2020
DOI: 10.21037/gs-2019-catp-22
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese reporting system for thyroid aspiration cytology 2019 (JRSTAC2019)

Abstract: We introduce the Japanese reporting system for thyroid aspiration cytology 2019 (JRSTAC2019) proposed by the Japan Association of Endocrine Surgery and the Japanese Society of Thyroid Pathology.Pathological classification and recommended clinical management for thyroid nodules in Japan are different from those described in the World Health Organization classification or the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC). Therefore, it was necessary to develop a reporting system adapted for Japan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Concerning thyroid cytopathology, Hirokawa, one of the authors, reported as The Japanese reporting system for thyroid Amyloid deposition is present in the stroma. aspiration cytology 2019 (JRSTAC2019) [16] as the modified version of the Bethesda System. JRSTAC2019 explained the contents of the cytological aspects of the Japanese General Rules, which is widely used in Japan.…”
Section: Cytology Reporting Format In the Japanese General Rulesmentioning
confidence: 99%
“…Concerning thyroid cytopathology, Hirokawa, one of the authors, reported as The Japanese reporting system for thyroid Amyloid deposition is present in the stroma. aspiration cytology 2019 (JRSTAC2019) [16] as the modified version of the Bethesda System. JRSTAC2019 explained the contents of the cytological aspects of the Japanese General Rules, which is widely used in Japan.…”
Section: Cytology Reporting Format In the Japanese General Rulesmentioning
confidence: 99%
“…In addition to the Italian classification and the Bethesda system, other thyroid cytology reporting systems frequently used by pathologists are The Guidance On The Reporting Of Thyroid Cytology Specimens from The UK Royal College Of Pathologists proposed in 2009 and revised in 2016 [7] and The Japanese reporting system for thyroid aspiration cytology proposed by the Japanese Thyroid Association in 2019 [8].…”
Section: British and Japanese Reporting Systems For Thyroid Cytologymentioning
confidence: 99%
“…In order to distinguish nodules to be sent for surgical treatment from those to be observed over time with clinical and ultrasonographic examinations, classifications (or reporting systems) based on cytological criteria have been drawn up. Among the reporting systems, the Italian SIAPeC-AIT classification, in its latest version updated in 2014/(CI14) and The Bethesda System for Reporting Thyroid Cytopathology, proposed in 2007 and updated in 2017 (TBSRTC) are among the most widely used in the world [5,6] together with the Guidance On The Reporting Of Thyroid Cytology Specimens from The UK Royal College Of Pathologists [7] and The Japanese reporting system for thyroid aspiration cytology [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid nodules are a common clinical finding, with palpable thyroid nodules detected in 1% of men and 5% of women in iodine-sufficient regions of the world [1][2][3][4][5]. However, with the increasing use of radiologic screening, one or more thyroid nodules are found in 60-70% of the population [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…FNA has proven to be an important tool in the management of thyroid nodules. Currently, thyroid FNA cytology is reported in a standardized fashion by employing one of the known tiered classification systems [3,[11][12][13][14]. While FNA cytology can effectively differentiate between benign and malignant thyroid lesions in up to 75% of cases, 20-30% of aspirated nodules are reported as indeterminate for malignancy [14,15].…”
Section: Introductionmentioning
confidence: 99%